Strategi Komunikasi Pariwisata Dalam Meningkatkan Pengunjung Destinasi Glamping Wira Garden Bandar Lampung - ROYNALDO SIMANULANG; Budhi Waskito; Hanindyalaila Pienrasmi (Journal of Innovative and Creativity, 2025)
This study discusses the application of SWOT analysis to tourism communication strategies in increasing visits to the Wira Garden Glamping destination. The objectives of this study are 1) To analyze the weaknesses and strengths of tourism communication owned by the Wira Garden Bandar Lampung glamping destination manager. 2) To analyze the opportunities and challenges of tourism communication faced by the Wira Garden Bandar Lampung glamping destination manager. To find out the current development strategy for Lasonrai Beach tourism. 3) To analyze tourism communication strategies that can be used to increase tourist visits to the Wira Garden Bandar Lampung glamping destination. This research is a type of field research using a qualitative descriptive approach. The data used in this study were obtained from primary data and secondary data. Data collection techniques used are observation, interviews and documentation and will be analyzed by means of data reduction, data presentation, and drawing conclusions. The results of this study indicate that 1) Strengths and Weaknesses of Tourism Communication are known that the management of Glamping Wira Garden has several strengths, a unique glamping concept that has not been widely found in the surrounding area, and the existence of social media (Instagram and TikTok) that have been used as promotional media. 2) Opportunities and Challenges of Tourism Communication. This study also found that current tourism trends tend to be directed towards nature-based and experience-based tourism, which is a great opportunity for Wira Garden to develop. 3) The tourism communication strategy implemented by the management of Glamping Wira Garden Bandar Lampung tends to utilize internal strengths, such as the uniqueness of the glamping concept and natural potential, to attract tourists through social media.